Pain and anxiety in patients undergoing preventive colon endoscopy - Bazaliński, Dariusz; Kaczmarska, Dorota; Bujalski, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : The development of diagnostics, especially endoscopic procedures, together with society’s greater awareness about prevention of cancer, including alimentary tract malignancies, has led to the situation where many people decide to undergo preventive colon cancer examination. So far no agreement regarding international standards for screening methods in colon cancer has been reached. However, there is evidence that preventive endoscopy of the lower part of the alimentary system reduces the incidence rate in colon cancer. This method is better accepted than other preventive examinations since the recommended time interval between successive colonoscopies is 10 years, while the occult blood test should be performed at least once a year. Aim of the study : The objective of this work was to evaluate anxiety level and pain intensity during preventive colon endoscopy. Material and methods : The study was performed using a diagnostic survey. The questionnaire, designed by the authors, consisted of two parts. Also, the STAI questionnaire and NRS pain intensity scale were applied. Additionally, medical records were reviewed from the viewpoint of pharmacotherapy, the depth of the examined colon, and diagnosed changes. Obtained information was analysed statistically with Pearson’s 2 test. The study took place in Podkarpacki Oncology Centre in Brzozow and lasted for 9 months (from April to December 2008). The number of colonoscopy examinations in patients qualified for outpatient endoscopic procedures within the colon screening programme financed by the National Health Insurance was 340. Conclusions : Women reported pain during the examination more frequently than men. The most common pain experiences reported by patients included: bloating, discomfort, and local abdominal pain. Mean score on the NRS pain scale was 4.5 points. Therefore, it may be assumed that the examination was moderately painful. As far as anxiety level was concerned, inhabitants of rural areas feared the examination more often than patients from towns. A high level of anxiety was associated with a subjective increase of pain. Patients with university education had a significantly lower level of anxiety.